1997
DOI: 10.1007/s004410050757
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of gastrin in cancer cells expressing gastrin/CCK-B receptor

Abstract: Endocytosis of gastrin was studied in a number of gastrin-receptor-expressing cell lines by confocal laser scanning microscopy (CLSM) with the aid of a biologically active fluorescent derivative, rhodamine green heptagastrin. Rapid clustering (within 4-7 min) and internalization of fluorescent ligand upon binding at room temperature and 37 degrees C were observed in the rat pancreatic acinar carcinoma cell line AR42J, human gastric carcinomas AGS-P and SIIA, human colon carcinomas HCT116 and HT29, and in NIH/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Biased ligands identified in the current study should be able to block ␤-arrestin-dependent signaling and effects downstream of the CCK2R. This is of high importance because the CCK2R is expressed in a large variety of cancers and, according to a previous study (19), undergoes internalization in gastric, pancreatic, and colonic cell lines that endogenously express this receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biased ligands identified in the current study should be able to block ␤-arrestin-dependent signaling and effects downstream of the CCK2R. This is of high importance because the CCK2R is expressed in a large variety of cancers and, according to a previous study (19), undergoes internalization in gastric, pancreatic, and colonic cell lines that endogenously express this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we delineated the role and mechanism of action of RGS-2 (regulator of G-protein signaling-2) in CCK2R-induced inositol phosphate production (17). However, the mechanism and consequences of CCK2R regulation at the cell surface by its natural ligands or by synthetic ligands are not yet precisely known (18,19).…”
mentioning
confidence: 99%
“…Both CCK1R and CCK2R have been shown to undergo internalization in pancreatic acini and transfected NIH 3T3 or CHO cells (177,418,522). Interestingly, in the case of CCK1R, agonist and antagonistinduced desensitization of CCK1R were described (417).…”
Section: B Activation Mechanism and Regulationmentioning
confidence: 99%
“…The receptors and ligands are sorted in endosomes (11). Both CCK-A and CCK-B receptors are recycled to the cell surface with very high efficiency, whereas the peptide ligands end up in lysosomes, where presumably they are degraded (11,29). This paper reports on the synthesis, processing, and selective toxicity of drugs directed to CCKBR-positive cells.…”
Section: More Toxic To Cholecystokinin Type B Receptor-positive Nih͞ mentioning
confidence: 99%
“…Subsequent studies in our laboratory, which used fluorescent-labeled heptagastrin and CCK-8 (11,28,29), showed that both CCKBR and CCK-A receptor agonists undergo internalization by endocytosis upon binding to the receptors. The receptors and ligands are sorted in endosomes (11).…”
Section: More Toxic To Cholecystokinin Type B Receptor-positive Nih͞ mentioning
confidence: 99%